DENTAL ERGONOMICS - Suwandi, Tjipto (Fakultas Kedokteran Gigi Universitas Jember, 2010)
Dental Ergonomic is a new brand of Medical and dental knowledge which dialing with various dental technologies and fisiologies. Dental profesional is suggested to aplly this Dental Ergonomic to anable the best treatment achived and satisfaction of patients.